2009
DOI: 10.1080/00343400903107736
|View full text |Cite
|
Sign up to set email alerts
|

Do Clusters Make a Difference? Defining and Assessing their Economic Performance

Abstract: Spencer G. M., Vinodrai T., Gertler M. S. and Wolfe D. A. Do clusters make a difference? Defining and assessing their economic performance, Regional Studies. This paper contributes to the literature on cluster dynamics by developing a new methodology for identifying clusters that is not dependent on United States-based definitions. This methodology is used to test if the geographical clustering of economic activities leads to superior industrial performance and regional competitiveness. The analysis produces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 27 publications
4
112
0
6
Order By: Relevance
“…There is a large empirical literature that has analysed various aspects of agglomeration impacts in terms of both Jacobs and MAR externalities. See, for example: GLAESER et al, (1992); AUDRETSCH and FELDMAN (1996); PACI and USAI (2000); DURANTON and PUGA (2001); GREUNZ (2004); MARTIN et al (2008b); SPENCER et al, (2009)…”
Section: Clusters and Cluster Policiesmentioning
confidence: 99%
“…There is a large empirical literature that has analysed various aspects of agglomeration impacts in terms of both Jacobs and MAR externalities. See, for example: GLAESER et al, (1992); AUDRETSCH and FELDMAN (1996); PACI and USAI (2000); DURANTON and PUGA (2001); GREUNZ (2004); MARTIN et al (2008b); SPENCER et al, (2009)…”
Section: Clusters and Cluster Policiesmentioning
confidence: 99%
“…Enright, 1996;Spencer et al, 2010) include a degree of specialisation in a particular industry (measured by employment), co-location of the specialized industry and other related industries, and scale or critical mass in the cluster. There are however many deep-seated controversies about conceptual and empirical questions of what clusters are and how they can be identified, how they emerge and evolve, why they matter and how they can be used by policy (Pitelis et al, 2006).…”
Section: What Are Clusters?mentioning
confidence: 99%
“…A more limited number of studies have tried to empirically demonstrate the benefits of clustering on growth and productivity. For instance, Spencer et al (2010), using a data set for 300 industries in 140 city-regions in Canada, found that industries located in areas with critical mass of related industries tend to display higher incomes and rates of growth compared with those located in non-clustered settings. In a comparative study of clustering in the US and UK computer industries, Baptista and Swann (1999) found that firms in strong clusters tend to grow faster.…”
Section: The Economic Importance Of Clustersmentioning
confidence: 99%
“…This has the advantage that the concept can be integrated into an input-output framework, in which input-output linkages, i.e. the flow of Another approach is offered by Spencer et al (2010). Their cluster identification concept is based on the application of the location quotient -a measure for regional specialization in a specific industry -and takes regional and national variations in economic structures, intersectoral relations and historical contexts into account.…”
Section: Insight Into the Theory Of Agglomeration Advantagesmentioning
confidence: 99%
“…Thereby, industries were, in general, classified according to the official sector classification system. Only a few studies, for example by Spencer et al (2010) or Peri/Cuñat (2001), analysed the regional economic impact of clustered industries or, more precisely, the co-location of customers and suppliers of intermediate goods. The present model approach builds on the previous studies.…”
Section: Introductionmentioning
confidence: 99%